Research on Green Transport Mode of Chinese Bulk Cargo Based on Fourth-Party Logistics - Jixiao Wu; Yinghui Wang; Wenlu Li; Haixia Wu (Journal of Advanced Transportation)
Due to the problems such as the excessive proportion of road transport and extreme carbon emission situation of China’s transport structure adjustment, this paper combines the fourth-party logistics with the bulk cargo green transport. It is advancing the adjustment of China’s bulk cargo transport structure using fourth-party logistics. This paper improves the particle swarm optimization algorithm to compare the integrated cost and carbon emissions of different bulk fourth-party transport networks to verify the benefits of the fourth-party logistics on bulk cargo transport networks’ cost reduction and emission reduction. The results show that using the fourth-party logistics model to promote the transfer of cargoes from road to rail can reduce the integrated cost of the transport network, reduce carbon emissions, and achieve green transport.